Teacher training as a driver for the digital transformation at Universidad Estatal a Distancia (UNED), Costa Rica - Castro - Granados, Alejandra (2025)
This essay analyzes the impact of teacher training on the pedagogical use of technological tools, as well as on the design and mediation of virtual learning environments in distance higher education. It is based on the recognition that digital transformation in teaching requires more than infrastructure; it demands continuous professional development, contextualized pedagogical support, and instructional strategies that foster active and meaningful learning. Drawing on recent studies, it examines the challenges and opportunities of this transition and proposes a comprehensive vision that integrates digital competencies, didactic innovation, and institutional commitment. It concludes that teacher training is not an optional complement, but the foundation of genuine educational transformation.